Optimization of Galangal Essential Oil Stik Balsam Formula (Alpinia galanga (L.) Willd.): [Optimization of Galangal (Alpinia galanga (L.) Willd.) Essential Oil Stick Balsam Formula] - Ernestine Arianditha Pranasti; Ayuningtyas, Nurista Dida; Pramitaningastuti, Anastasia S.; Cahaya, Gabriella Lisye (Universitas Pelita Harapan, 2025)
High occurrence of muscle pain has encouraged the development of practical natural solutions, such as stick balm formulated with galangal (Alpinia galanga) essential oil, which shows potential as a topical analgesic agent. This study formulated galangal stick balm to relieve muscle pain while meeting physical requirements and user preferences. The formulation involved variations in base composition (solid paraffin and white petrolatum) and methyl salicylate concentration to evaluate physical characteristics such as pH, homogeneity, melting point, and irritation potential. A hedonic test was conducted to determine the most preferred formula. Results showed that all formulas had safe pH levels (4.5–6.5), good homogeneity, melting points between 57–60°C, and caused no skin irritation in volunteers. Hedonic testing identified Formula F4 as the best candidate based on aroma, warmth, and texture. Therefore, galangal essential oil stick balm has promising potential to be developed as a safe, stable, and user-friendly analgesic topical preparation. Bahasa Indonesia Abstract: Tingginya kasus nyeri otot mendorong pengembangan solusi alami yang praktis, seperti balsam stik berbahan minyak atsiri lengkuas (Alpinia galanga), yang memiliki potensi sebagai agen analgetik topikal. Penelitian ini merumuskan formulasi balsam stik lengkuas untuk meredakan nyeri otot yang memenuhi syarat fisik dan disukai. Formulasi dilakukan dengan variasi komposisi basis (paraffin solid dan vaselin album) dan variasi metil salisilat untuk mengevaluasi karakteristik fisik seperti pH, homogenitas, titik lebur, dan potensi iritasi. Uji kesukaan dilakukan untuk melihat formula mana yang paling disukai. Hasil menunjukkan bahwa seluruh formula memiliki pH dalam rentang aman (4,5–6,5), homogenitas yang baik, titik lebur antara 57–60°C, serta tidak menimbulkan iritasi pada kulit sukarelawan. Uji kesukaan menunjukkan Formula F4 sebagai kandidat terbaik berdasarkan aroma, kehangatan, dan tekstur. Dengan demikian, balsam stik minyak atsiri lengkuas berpotensi dikembangkan sebagai sediaan antinyeri yang aman, stabil, dan disukai pengguna.